Pendekatan Pembelajaran Berbasis Al-Qur’an Qur’annic-Based Learning Approach - Nur Afif; Firdaus Firdaus; Agus Nur Qowim (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study discusses qur'an-based learning approaches. This research is a qualitative type with a literary analysis approach (literature study) that concludes that the Qur'an requires two approaches to learning, as two types of learning approaches in education theory are called teacher centered and student centered. But the Qur'an requires a more portion of the student centered approach considering the span of human age between the maturity period of intelligence development is longer than the age of physical growth, Moreover, the case study of verses that shed more on the maturity of intelligence that indicates independence as the case of Ulul Albab. In addition, the Qur'an indicates that the variety of learning approaches pay attention to at least three potentials of humans who are interlinked in the process of learning interaction, namely the potential of remembrance (affective), thinking (cognitive) and charity shaleh (Psychomotoric). Keywords: Approach, Learning, Qur’an-Based